(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Color plays a pivotal role in design, impacting both aesthetics and psychological responses. Understanding how colors affect mood and perception enables designers to make informed decisions that evoke the desired emotional response from their audience. This paper explores the foundations of color theory, examining the psychological associations of primary, secondary, and tertiary colors. It further analyzes how cultural and contextual factors influence color perception and offers insights into applying color theory effectively in various design fields such as graphic design, interior design, and branding.